Neoadjuvant carboplatin in patients with triple-negative and HER2-positive early breast cancer (GeparSixto; GBG 66): a randomised phase 2 trial - Von Minckwitz, Gunter; Schneeweiss, Andreas; Loibl, Sibylle; Salat, Christoph; Denkert, Carsten; Rezai, Mahdi; Blohmer, Jens U.; Jackisch, Christian; Paepke, Stefan; Gerber, Bernd; Zahm, Dirk M.; Kummel, Sherko; et al. (Lancet Oncology, 2014)
Preclinical data suggest that triple-negative breast cancers are sensitive to interstrand crosslinking agents, and that synergy may exist for the combination of a taxane, trastuzumab, and a platinum salt for HER2-positive breast cancer. We therefore aimed to assess the efficacy of the addition of carboplatin to neoadjuvant therapy for triple-negative and HER2-positive breast cancer.Patients with previously untreated, non-metastatic, stage II-III, triple-negative breast cancer and HER2-positive breast cancer were enrolled. Patients were treated for 18 weeks with paclitaxel (80 mg/m(2) once a week) and non-pegylated liposomal doxorubicin (20 mg/m(2) once a week). Patients with triple-negative breast cancer received simultaneous bevacizumab (15 mg/kg intravenously every 3 weeks). Patients with HER2-positive disease received simultaneous trastuzumab (8 mg/kg initial dose with subsequent doses of 6 mg/kg intravenously every 3 weeks) and lapatinib (750 mg daily). Patients were randomly assigned in a 1:1 ratio with dynamic allocation and minimisation, stratified by biological subtype and Ki-67 level to receive, at the same time as the backbone regimens, either carboplatin (AUC 1·5 [2·0 for the first 329 patients] once a week) or no carboplatin. The primary endpoint the proportion of patients who achieved a pathological complete response (defined as ypT0 ypN0), analysed for all patients who started treatment; a p value of less than 0·2 was deemed significant for the primary endpoint. This trial is registered with ClinicalTrials.gov, number NCT01426880.296 patients were randomly assigned to receive carboplatin and 299 to no additional carboplatin, of whom 295 and 293 started treatment, respectively. In this final analysis, 129 patients (43·7%, 95% CI 38·1-49·4) in the carboplatin group achieved a pathological complete response, compared with 108 patients (36·9%, 31·3-42·4) without carboplatin (odds ratio 1·33, 95% CI 0·96-1·85; p=0·107). Of the patients with triple-negative breast cancer, 84 (53·2%, 54·4-60·9) of 158 patients achieved a pathological complete response with carboplatin, compared with 58 (36·9%, 29·4-44·5) of 157 without (p=0·005). Of the patients with HER2-positive tumours, 45 (32·8%, 25·0-40·7) of 137 patients achieved a pathological complete response with carboplatin compared with 50 (36·8%, 28·7-44·9) of 136 without (p=0·581; test for interaction p=0·015). Haematological and non-haematological toxic effects that were significantly more common in the carboplatin group than in the no-carboplatin group included grade 3 or 4 neutropenia (192 [65%] vs 79 [27%]), grade 3 or 4 anaemia (45 [15%] vs one [<1%]), grade 3 or 4 thrombocytopenia (42 [14%] vs one [<1%]), and grade 3 or 4 diarrhoea (51 [17%] vs 32 [11%]); carboplatin was more often associated with dose discontinuations (141 [48%] with carboplatin and 114 [39%] without carboplatin; p=0·031). The frequency of grade 3 or 4 haematological events decreased from 82% (n=135) to 70% (n=92) and grade 3 or 4 non-haematological events from 78% (n=128) to 59% (n=77) in the carboplatin arm when the dose of carboplatin was reduced from AUC 2·0 to 1·5.The addition of neoadjuvant carboplatin to a regimen of a taxane, an anthracycline, and targeted therapy significantly increases the proportion of patients achieving a pathological complete response. This regimen seems to increase responses in patients with triple-negative breast cancer, but not in those with HER2-positive breast cancer.GlaxoSmithKline, Roche, and Tev
EVALuna2:17513